ANALISIS ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP RETURN SAHAM PT. MUSTIKA RATU Tbk - Maria Esomar; Imanuela Tuapattinaja (Soso-Q : Jurnal Manajemen, 2019)
The company's financial performance can be used by investors to predict stock returns. The purpose of this research is to find out the effect of Eva and Mva on stock returns. This research is a research using a quantitative approach. This study uses secondary data in the form of financial statements sourced from the Indonesia Stock Exchange (BEI) publication report. The data used in this study are financial reports audited in 2013-2017. From the results of the study showed that the Economic Value Added (EVA) of PT. Mustika Ratu Tbk during 2013-2017 was not optimal because the results of Negative EVA or EVA <0. While Market Value Added (MVA) of PT. Mustika Ratu Tbk during 2013-2017 is good because the results of MVA, although it tends to decrease, but the results are positive or MVA> 0. Kata Kunci: Return Saham, Economic Value Added (EVA) dan Market Value Added (MVA)